The identification of beta-thalassemia mutants in Brazilians with high Hb F levels - Zamaro, Paula J. A.; Bonini-Domingos, Claudia R. [UNESP] (Associação Brasileira de Hematologia e Hemoterapia e daSociedade Brasileira de Transplante de Medula Óssea, 2010)
As hemoglobinopatias são um grupo de afecções genéticas que representam problema de saúde pública em muitos países em que sua incidência é alta, com significativa morbidade. Objetivamos identificar defeitos moleculares que pudessem explicar o perfil laboratorial obtido por eletroforese e HPLC com Hb F elevada, em um grupo de indivíduos adultos sem sinais ou sintomas de anemia. Encontramos cinco diferentes mutações que originam beta talassemia por PCR-ASO: três casos com CD 6 (-A), um CD 39, um IVS 1-5, um -87 todas de origem mediterrânea, e um IVS II-654 de origem asiática. As mutações CD 6 (-A), -87 e IVS II-654 foram descritas pela primeira vez na população brasileira.

Hemoglobinopathies are a heterogeneous group of genetic disorders which represent a public health problem, with significant morbidity, in countries where the prevalence is high. This study aimed at identifying molecular abnormalities that might explain the laboratorial profile obtained using electrophoresis and high performance liquid chromatography in a group of individuals without signs or clinical symptoms of anemia. Five different mutations for beta-thalassemia were found using PCR-ASO: three cases with CD 6 (-A), one CD 39, one IVI I-6, one -87 (mutations originating in the Mediterranean region) and one IVS II-654 (mutation originating in Asia). This is the first time that the CD 6 (-A), -87 and IVS II-654 mutations have been described in the Brazilian population.
Identificação de mutantes de beta talassemia em grupo de indivíduos com Hb Fetal aumentada da população brasileira
Keywords: Beta-thalassemia; Fetal hemoglobin; Molecular biology; Talassemia beta; Hemoglobina fetal; Biologia molecular